Analysis of Employee Recruitment at ID Food (BUMN) 2020-2022 - Fransisca Tutii Rahayu (Nomico, 2024)
This study analyzes the recruitment of ID FOOD (BUMN) in the period 2020-2022. The data used comes from the company's annual report. This analysis includes employee recruitment programs, and the impact of recruitment on the company. The method used is qualitative research with descriptive analysis technique of literature study. The object of this research is the recruitment process carried out by the ID Food (PERSERO) company. The data collection technique used in this research is to use secondary data by collecting relevant research articles. The results showed that ID Food (PERSERO) experienced a decrease in employees in 2020 and 2021 due to employees retiring and resigning. There is no data disclosure so that there are differences in the number of employees in the 2020 financial stAatements and 2021 financial statements.  The increase in 2022 was due to five companies being built. The quality of new employees at ID Food (PERSERO) is said to be lacking because many employees resigned in 2021 even though in 2022 the company opened a new subsidiary. If the employee is qualified, the employee will be transferred instead of resigning. However, researchers can find out that there are irregularities in the financial statements where there is no match in the number of employees in the 2020 financial statements and 2021 financial statements. In addition, the 2023 financial statements have not been published. Even though the ID Food company is categorized as a go public company which should have sent the latest financial statements.